READING THE WORLD. HENRYK WANIEK – AUTHOR, PAINTER, OUTSIDER - Ćwiklak, Kornelia (Porównania, 2019)
This text is devoted to the works of Henryk Waniek, an artist of a remarkably rich and coherent literary and painting output merged by the idea of discovering the spiritual basis of our reality. The first part of this article discusses his activity as co-founder of the Oneiron Circle belonging to the Silesian artistic underground of the 1960s and 1970s, here related to as an essential context and prediction of his coming work. The second part analyses Waniek’s prose, especially the categories of artistic memory, nature and consciousness. I propose the thesis that Waniek in his work brings together (seemingly) opposing models: an outsider model and an obligatory model. With time, the author takes the side of an artist as a memory guard more and more. However, it is crucial to treat art as initiation. Both attitudes are united in the figure of the outsider following his own path through Silesia which the artist considered to be the central point of his work.